Effect of natural coagulant application on microfiltration performance in treatment of secondary oxidation pond effluent - Saed, Katayon; Megat Mohd Noor, Megat Johari; Wai, KienTat; Ghazali, Abdul Halim; Mohammed, Thamer Ahmed; Yusuf, Badronnisa (Elsevier, 2007)
A secondary oxidation pond effluent was treated using hollow-fibre crossflow microfiltration and coagulation process. Preliminary tests were carried out to find the optimum dosage of Moringa oleifera (a natural coagulant) for the coagulation process. Optimum dosage of Moringa oleifera was recorded as 100 mg/L for turbidity of secondary oxidation pond effluents ranging between 30 and 100 NTU. Turbidity removal achieved ranged between 50 and 57%. The performance of microfiltration coupled with coagulation using optimum dosage of Moringa oleifera was investigated. Better flux performance and lower rate of fouling were achieved when combining microfiltration with coagulation. Pseudo-steady state flux of 3 L/m2.h at a relatively constant suction pressure of less than 0.6 bar was obtained after 300 h of filtration time. Results showed that the values of COD, BOD5, alkalinity, VSS, TS, turbidity and pH in the filtrate were not influenced significantly by incorporation of coagulation using Moringa oleifera. The filtrate quality of about 50 mg/L COD, 25 mg/L BOD5, 2 mg CaCO3/L alkalinity, 1 NTU turbidity, 1 mg/L TSS and VSS respectively was produced when using microfiltration with and without coagulation.